Faktor-faktor Yang Mempengaruhi Minat Pemanfaatan Sistem Informasi Pengelola Keuangan Daerah (SIPKD)(Studi Kasus Pada Pegawai Negeri Sipil Pemerintah Kota Surakarta) - Saputro, Rangga Yudas (2016)
One of government implementation applying exploiting of information technology for the activity accountancy area of one day of was usage area finance organizer information system. This research was aim to analyse the factors influencing enthusiasm of area finance organizer information system exploit in in Surakarta City. This research was using analysis and survey descriptive with quantitative approach, by the data source in the form of primary data obtained from questioner. Sum up the sample research counted 58 sample taken by purposive sampling. Analyzer used cover data quality test, classic assumption test, multiple linear regressions analyze and hypothesis test covering F test, coefficient determinasi R2 test, and t test. The results of analysis can be conclusion that the factors influencing enthusiasm of exploiting of organizer area finance information system in Surakarta City including performance expectation, effort expectation and social factor. Where third independent variables have an significant effect to enthusiasm of area finance organizer information system exploit in Surakarta City, this matter was shown by p value was each variable < 0,05. So that hypothesis from H1 until H3 was truth acceptable. Keyword: enthusiasm of area finance organizer information system exploit in Surakarta City, mance expectation, effort expectation and social factor